Simulation of an Operating Machine in Dust Chamber - Tollár, Sándor; Bolló, Betti (International Journal of Engineering and Management Sciences, 2019)
Auxiliary equipment used in the automotive industry, such as generator, air conditioner, or starter, is often exposed to harsh conditions, for example splash water, frost, or serious dust load. Therefore, these auxiliary devices are intended to be prepared by the manufacturers to these conditions. The topic of this paper is a part of the analysis of the dust control of generators, which in principle is no different from the examination of other equipment. The flow around the generator and in the dust chamber was simulated by Ansys FLUENT.